Implementation of Post-Certification Professional Teacher Training ot MTSN 1 Model Padangsidimpuan - Hennilawati, Hennilawati; Surbakti, Ernawati Br; Harahap, Eli Marlina; Kamisah, Kamisah; Pohan, Sahrudin (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This research aims to describe the implementation of post-certification professional teacher training at MTsN 1 Model Padangsidimpuan. This type of research uses a qualitative approach with descriptive analytical study methods. Data collection used observation, interview and documentation study methods. Next, the data was analyzed using data reduction techniques, data presentation, and drawing conclusions. To test the validity of the data, data triangulation techniques were used. The results of this research concluded that there were 61 certified teachers at MTsN 1 Model Padangsidimpuan, consisting of 60 Civil Servants (PNS) and 1 Non-Civil Servant (honorary). Certified teachers at MTsN 1 Model Padangsidimpuan undergo training after they are certified to support professionalism in the implementation of education. The training includes laboratory training, Class Action Research (CAR), Subject Teacher Conference (MGMP), increasing the competence of subject teachers, implementation of the 2013 curriculum, pre-service, integrated information technology, personnel administration, and personality training.